Newborn amygdalar volumes are associated with maternal prenatal psychological distress in a sex-dependent way - Satu J Lehtola; Jetro J Tuulari; Noora M Scheinin; Linnea Karlsson; Riitta Parkkola; Harri Merisaari; John D Lewis; Vladimir S Fonov; D.Louis Collins; Alan Evans; Jani Saunavaara; Niloofar Hashempour; et al. (Netherlands, 2022)
Maternal psychological distress during pregnancy (PPD)1 has been associated with changes in offspring amygdalar and hippocampal volumes. Studies on child amygdalae suggest that sex moderates the vulnerability of fetal brains to prenatal stress. However, this has not yet been observed in these structures in newborns. Newborn studies are crucial, as they minimize the confounding influence of postnatal life.
We investigated the effects of maternal prenatal psychological symptoms on newborn amygdalar and hippocampal volumes and their interactions with newborn sex in 123 newborns aged 2–5 weeks (69 males, 54 females). Based on earlier studies, we anticipated small, but statistically significant effects of PPD on the volumes of these structures. Maternal psychological distress was measured at gestational weeks (GW)2 14, 24 and 34 using Symptom Checklist-90 (SCL-90, anxiety scale)3 and Edinburgh Postnatal Depression Scale (EPDS)4 questionnaires.
Newborn sex was found to moderate the relationship between maternal distress symptoms at GW 24 and the volumes of left and right amygdala. This relationship was negative and significant only in males. No significant main effect or sex-based moderation was found for hippocampal volumes.
This newborn study provides evidence for a sex-dependent influence of maternal psychiatric symptoms on amygdalar structural development. This association may be relevant to later psychopathology.